Performance of algorithms that reconstruct missing transverse momentum in √s=8 TeV proton-proton collisions in the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
The reconstruction and calibration algorithms used to calculate missing transverse momentum (EmissTETmissE_{\text {T}}^{\text {miss}} ) with the ATLAS detector exploit energy deposits in the calorimeter and tracks reconstructed in the inner detector as well as the muon spectrometer. Various strategies are used to suppress effects arising from additional proton-proton interactions, called pileup, concurrent with the hard-scatter processes. Tracking information is used to distinguish contributions from the pileup interactions using their vertex separation along the beam axis. The performance of the EmissTETmissE_{\text {T}}^{\text {miss}} reconstruction algorithms, especially with respect to the amount of pileup, is evaluated using data collected in proton-proton collisions at a centre-of-mass energy of 8 TeVTeV\text {TeV} during 2012, and results are shown for a data sample corresponding to an integrated luminosity of 20.3fb−120.3fb−120.3\, fb^{-1}. The simulation and modelling of EmissTETmissE_{\text {T}}^{\text {miss}} in events containing a Z boson decaying to two charged leptons (electrons or muons) or a W boson decaying to a charged lepton and a neutrino are compared to data. The acceptance for different event topologies, with and without high transverse momentum neutrinos, is shown for a range of threshold criteria for EmissTETmissE_{\text {T}}^{\text {miss}} , and estimates of the systematic uncertainties in the EmissTETmissE_{\text {T}}^{\text {miss}} measurements are presented.